2012
DOI: 10.1167/iovs.11-8445
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Immunomodulation Retards Regeneration of Surgically Transected Corneal Nerves

Abstract: Immunomodulation with CsA reduces the expression of cytokines (IL6) in the cornea and retards regenerative sprouting from transected corneal stromal nerve trunks. In addition, CsA has a direct growth inhibitory action on neurites as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 53 publications
(42 reference statements)
3
39
0
Order By: Relevance
“…Further, in an in vivo mouse model of corneal abrasion, twicedaily 0.05% CsA retarded sprouting of transected stromal nerves while suppressing corneal inflammation [53]. This study also found that 0.0005% CsA directly inhibited neurite outgrowth in cultured mouse trigeminal ganglion cultures.…”
Section: Cyclosporine Asupporting
confidence: 59%
See 1 more Smart Citation
“…Further, in an in vivo mouse model of corneal abrasion, twicedaily 0.05% CsA retarded sprouting of transected stromal nerves while suppressing corneal inflammation [53]. This study also found that 0.0005% CsA directly inhibited neurite outgrowth in cultured mouse trigeminal ganglion cultures.…”
Section: Cyclosporine Asupporting
confidence: 59%
“…CsA is from the calcineurin family of immune suppressants. It blocks T-cell proliferation and down regulates IL-2 receptor expression and gene transcription [53].…”
Section: Cyclosporine Amentioning
confidence: 99%
“…29 We, as well as others, have reported that regenerating nerves in the cornea do not follow pre-existing tracks; therefore, the appearance of new fluorescent nerve fibers in a new pattern signifies nerve regeneration. [14][15][16] We visualized two forms of stromal nerve neurotoxicity. Reversible neurotoxicity (axonopathy) was characterized by Western blot analyses of corneal lysate showed an increase in abundance of proteins associated with inflammation (IL6 and CD3) at 1 week and reduced abundance at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…16,[24][25][26] On day 1, trigeminal neuronal cells (1 · 10 3 ) were plated in the central compartment. The side compartments were filled with a mixture that was identical except that it also contained cytosine arabinoside (AraC, 0.3 lM; Sigma).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 1 more Smart Citation